Surgical Treatment of Mucoepidermoid Carcinoma of the Lacrimal Sac. (March 2014) - Yuksel, Dilek; Kosker, Mustafa; Saribas, Ferhat; Simsek, Saban
Abstract Purpose: We report successful management of a case with high-grade mucoepidermoid carcinoma of the lacrimal sac managed by aggressive soft tissue and bony resection with adjuvant radiotherapy. Methods: Case report. Results: A 32-year-old man was referred to us with a two-year history of epiphora and slow-growing mass in the area of the lacrimal sac. On physical examination, a firm and nontender mass was visible overlying the area of the right lacrimal sac. Computed tomography and magnetic resonance imaging confirmed a 30 mm × 15 mm, well-enhanced soft tissue mass occupying the lacrimal fossa and extending to include the nasolacrimal duct, and FNA biopsy of the mass demonstrated high-grade mucoepidermoid carcinoma. On this basis, the tumor, lacrimal sac, and nasolacrimal duct were removed en bloc with the frontal process of the maxilla, lateral nasal wall, lacrimal fossa, ethmoids, and anterior part of the medial orbital wall with two intraoperative frozen section examinations. Postoperatively, the patient received adjuvant radiotherapy. The clinical evaluation and positron emission tomography at 38 months showed recovery and no recurrence of the disease. Conclusions: MEC of the lacrimal sac is extremely rare and spreads locally in an aggressive manner. Despite the fact that orbital exenteration have generally been recommended for these tumors, radical surgical resections with external radiation therapy might be effective. In our case, despite the high-grade MEC, the patient underwent successful radical surgical excision and postoperative adjuvant external radiotherapy. As a result, we achieved an aesthetically satisfying result by preserving the eye and the vision.